Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/pcn.12006
|View full text |Cite
|
Sign up to set email alerts
|

Self‐awareness of executive dysfunction in Huntington's disease: Comparison with Parkinson's disease and cervical dystonia

Abstract: This study assessed self-awareness of executive deficits in patients with Huntington's disease (HD) in comparison to patients with Parkinson's disease (PD) and with cervical dystonia (CD). Eighty-nine patientproxy pairs participated in the study (23 with HD, 25 with advanced PD, 21 with mild PD and 20 with CD). Executive function was assessed with the Stroop test and the Dysexecutive Questionnaire. Insight into executive impairment in HD is mildly affected, when compared to PD and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Two studies using the Dysexecutive Questionnaire demon-strated that HD patients could accurately rate proxies' but not their own behaviour [9,10], providing evidence of reduced self-awareness of behavioural change that cannot be attributable to generalized deficient judgement. A third study [13], which used the same questionnaire to compare insight in HD and PD, revealed only mild reduction in awareness for executive symptoms in HD, based on differences in patient and proxy ratings. It is possible though that relatively small group numbers resulted in lack of power to elicit significant differences.…”
Section: Insight Into Behavioural and Executive Impairmentmentioning
confidence: 98%
See 4 more Smart Citations
“…Two studies using the Dysexecutive Questionnaire demon-strated that HD patients could accurately rate proxies' but not their own behaviour [9,10], providing evidence of reduced self-awareness of behavioural change that cannot be attributable to generalized deficient judgement. A third study [13], which used the same questionnaire to compare insight in HD and PD, revealed only mild reduction in awareness for executive symptoms in HD, based on differences in patient and proxy ratings. It is possible though that relatively small group numbers resulted in lack of power to elicit significant differences.…”
Section: Insight Into Behavioural and Executive Impairmentmentioning
confidence: 98%
“…An additional 'preclinical' stage refers to people with the HD mutation who do not yet manifest overt clinical signs of disease. Awareness has been studied in both preclinical [2][3][4] and early-stage (stages 1-3) HD [2,3,[5][6][7][8][9][10][11][12][13][14].…”
Section: Identification and Classification Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations